A Child with Autism in a State School – A program for working with an autistic child in primary school. - Wieczorek, Emilia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
In the paper, the author discusses educational interactions focused on a child with autism. The first part of the study presents the characteristics of functioning of an autistic child, taking into account specific needs and difficulties. The research material was used to present the specificity of child’s functioning in certain developmental spheres: socio-emotional sphere, cognitive sphere, self-care, communication, sensory integration and motor integration. Bearing in mind a multi-profile diagnosis of the disorder and including various spheres of child’s functioning, the diagnosis was referenced to programming the process of support. The author concludes by presenting a reflection on dilemmas and challenges in education of autistic children.